Purchase intention for second-hand luxury goods: An empirical study of Chinese consumers - Yan, Guanfeng; Li, Yanjie; Zhang, Tianhai; Mu, Chenglin (PloS one, 2024)
Second-hand luxury goods feature both characteristics of luxury products like perceived value including social, emotional, and quality value, and second-hand goods like price-performance ratio. Enlarging the second-hand luxury market is of significance to protect the environment and save rare and valuable natural resources, and thus investigating the determinants of purchase intention is meaningful. From the perspective of the psychology of consumers, the influence of factors related to consumers (recycling awareness, subjective norms, attitudes, perceived behavioral control) and products (perceived value, price-performance ratio) on the intention to buy second-hand luxury goods is explored in this study through an online survey with Chinese consumers as a sample. The results are analyzed using the structural equation model (SEM) and show that consumers’ attitudes, perceived behavioral control, and recycling awareness will promote the intention of purchasing second-hand luxury goods, and the perceived value and price-performance ratio of second-hand luxury goods also have a positive impact on the purchase intention. However, there is no significant relationship between subjective norms and purchase intention. In addition, this study also explores the interrelationship between constructs and draws corresponding conclusions, providing references for the subsequent development of the second-hand luxury market.